Mammographic Trends of Pakistani Women Single Institutional Study - Jawad Ali Memon, Zubair Ali Memon, Javed Mehboob, Syed Mohammad Sibtain Shah, Aisha Siddiqua, Adnan Ahmed Qureshi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Breast carcinoma is the most common cancer and leading cause of cancer related death in women world wide.Mammography is currently the gold standard method to screen & diagnose the breast carcinoma at early stage. Materials and Methods: This retrospective cross sectional study is conducted in department of Diagnostic Radiology PUMHSW.SBA. Mammography examination including MLO & CCviews performed between 1January to 31st December 2020 are included in the study Results:Total of 579 women were referred for mammogram in the department in this 12 month duration.Of these 225 ladies had no breast related complains while 354 women complained of breast symptoms. The mean age of the patients was 46 years and the most common complain was mastalgia (44%). Total 2316 mammogram examinations of 1158 breasts was performed including 900 & 1416 in screening and diagnostic settings respectively.Out of 900 screening mammogram 58 (6.4%) patients are reported BIRADS IV. Conclusions:Our study noted reduce trend of screening mammogram in Pakistan women and 6.4% potential breast cancer can be detected in asymptomatic patients by screening mammogram